Bioeconomy: a new approach on biotechnology - Curtis, Gisela M.; Pérez, Gustavo A. (Nexo Revista Científica, 2021)
The analysis of the economy in biotechnology companies is becoming more important given that in recent years, as it has been expanding markets, and in some cases replacing traditional production techniques, improving, and simplifying work methodologies, its role within the process industry sector has been magnified. The multitude of variables to be considered in the improvement of operating costs, for the maximisation of benefits, indicate that there is still a long way to study this relatively new industry, which every day has more to offer.